1991
DOI: 10.1017/s0022112091002999
|View full text |Cite
|
Sign up to set email alerts
|

Lateral straining of turbulent boundary layers. Part 1. Streamline divergence

Abstract: Extensive experimental studies are presented of the effects of prolonged streamline divergence on developing turbulent boundary layers. The experiment was arranged as source flow over a flat plate with a maximum divergence parameter of about 0.075. Mild, but alternating in sign, upstream-pressure-gradient effects on diverging boundary layers are also discussed.It appears that two overlapping stages of development are involved. The initial stage covers a distance of about 20 initial boundary-layer thicknesses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
6
22
1
Order By: Relevance
“…(The profiles of k and −u v at At = 0.19 are included in Appendix B.) The Case SD results are consistent with the observations of Saddoughi & Joubert (1991), Pauley et al (1993) and Pompeo et al (1993), all of whom also found (for similar strength positive ∂W/∂z) that k and −u v increase slightly in the outer layer. At the time, there was significant uncertainty surrounding this result, due to the magnitude of the changes involved, and especially the potential influence in the experiments of streamwise and spanwise pressure gradients (see discussion in Pauley et al 1993).…”
Section: Reynolds Stressessupporting
confidence: 85%
See 3 more Smart Citations
“…(The profiles of k and −u v at At = 0.19 are included in Appendix B.) The Case SD results are consistent with the observations of Saddoughi & Joubert (1991), Pauley et al (1993) and Pompeo et al (1993), all of whom also found (for similar strength positive ∂W/∂z) that k and −u v increase slightly in the outer layer. At the time, there was significant uncertainty surrounding this result, due to the magnitude of the changes involved, and especially the potential influence in the experiments of streamwise and spanwise pressure gradients (see discussion in Pauley et al 1993).…”
Section: Reynolds Stressessupporting
confidence: 85%
“…Physically, this quantity can be viewed as a measure of how 'efficiently' the turbulence is able to utilize its kinetic energy to mix momentum across the mean velocity gradient, and thus how effectively the velocity fluctuations extract energy from the mean flow. As found in the experiments, both divergence (Saddoughi & Joubert 1991) and convergence (Panchapakesan et al 1997) cause outer-layer reductions in this quantity. The amount of the reduction found here varies with the sign and strength of A 33 (but is not proportional to |dβ * D /dt|).…”
Section: Turbulence Structuresupporting
confidence: 78%
See 2 more Smart Citations
“…Lateral divergence of boundary layer flows had been the subject of many investigations in the past [1][2][3][4][5]. One of the important conclusions of these studies [3][4][5] is the observed similarity with two-dimensional (2-D) flows even when the flow is turbulent (see for example, Pauley et al [4]), but with a thinner boundary layer compared to 2-D flows.…”
Section: Introductionmentioning
confidence: 99%